PENGARUH BEBAN KERJA, LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN - Adhika, I Nyoman Resa (Jurnal Ilmiah Satyagraha, 2025)
Employees work because they want to achieve something, and people hope that their work activities will lead them to a more satisfying situation than before. Job satisfaction is a psychological dimension that reflects a person's feelings about his job, namely his satisfaction with the suitability of his skills, abilities, and expectations for the job he holds. This study aims to explain the effect of workload, work environment, and compensation on employee job satisfaction at Cake Tha. The research population is all employees of Cake Tha. The sample in this study were 51 respondents. The data analysis technique used in this research is multiple linear regression analysis, which is tested using SPSS version 25. The results of this study indicate that workload has a negative and significant effect on job satisfaction, while the work environment and compensation each have a positive and significant effect on employee job satisfaction at Cake Tha.